The Possibility of an Island: Cold War Berlin as Charged Void, Landscape, and Mirage - Ioanna Angelidou (Histories of Postwar Architecture)
This paper is an attempt to provide an alternative and enriched genealogy of the utopian masterplan for Cold War era Berlin titled “The City in the City: Berlin, the Green Archipelago,” which the German architect Oswald Mathias Ungers developed in the latter half of the 1970s. This highly speculative project concerned with Berlin’s charged voids is dissected through a series of micro-histo[1]ries relative to the precedents that inform its fragmentary nature. Rather than a singularity or the product of a mastermind aided by disciples, as it has thus far been approached in the historiography of architecture, I shall position it as a centerpiece in a series of projects that unveil a shared repertory of formal operations and intellectual concerns. In tandem, the paper provides a lexicon for the term fragment as it has been perceived, theorized, and deployed in this sociopolitical and historical context, namely six distinct definitions, effects, and states of the fragment -  fractures, ruins, debris, lacunae, elements, and the notion of the unfinished. Through this scope, I consider the preoccupation with formal disjunction between parts and whole in architectural discourse during the second half of the twentieth century, particularly as it relates to the experience and design of the city. The latter, I argue, is informed by a critical stance to the technophiliac and abstrac[1]tionist tendencies of Modern architecture and a swerve towards a renewed interest in history and the palimpsestic quality of the urban tissue in the aftermath of World War II.